Ring Extensions with Finitely Many Non-Artinian Intermediate Rings - Noômen Jarboui; Naseam Al-Kuleab; Omar Almallah (Journal of Mathematics, 2020)
The commutative ring extensions with exactly two non-Artinian intermediate rings are characterized. An initial step involves the description of the commutative ring extensions with only one non-Artinian intermediate ring.